Multiple Frames of Reference Are Used During the Selection and Planning of a Sequential Joint Action - Ray, Matthew; Welsh, Timothy N. (Frontiers in Psychology, 2018)
Co-actors need to anticipate each other’s actions to successfully perform joint actions. The frames of reference (FOR) used to simulate a co-actor’s action could impact what information is anticipated. We hypothesized that co-actor’s would adopt their co-actor’s body-centered FOR, even when they do not share the same spatial orientation, so that they could anticipate body-related aspects of their co-actor’s task. Because it might be beneficial to plan joint actions based on environment and body-centered information, we hypothesized that individuals would utilize multiple FORs during response planning. To test these hypotheses, participants performed a sequential aiming task where the goal was to move a wooden dowel to one of four potential targets as quickly and accurately as possible. A cue was presented at the beginning of each trial that was either 25, 50 or 75% valid. Following the cue presentation, the first person to act (initiator) placed the wooden dowel, anywhere they liked, in the workspace. Then, the finisher performed their aiming movement from the location that the initiator had placed the dowel. The key dependent measure was the dowel placement of the initiator because it provided an index of how much the initiator attempted to facilitate the efficient performance of the finisher. The results revealed that individuals adopted an allocentric FOR (dowel placement was more biased towards cued locations as cue validity increased) and partially adopted their co-actor’s body-centered FOR (dowel placement was biased towards the finisher’s body, but not towards the co-actor’s contralateral space). In conclusion, multiple FORs can be used to anticipate both body- and environment-related information of a co-actor’s task. It may be difficult, however, for individuals to fully adopt their co-actor’s body-centered FOR when they have differing orientations.